Upgrade of the Argentine Islands INTERMAGNET observatory at Akademik Vernadsky station, Antarctica - A. Marusenkov; M. Leonov; V. Korepanov; S. Leonov; A. Koloskov; Ye. Nakalov; Yu. Otruba (Ukrainian Antarctic Journal, 2019)
The article describes the main features of upgrading the magnetometric complex based on the LEMI-025 variometer in January-April 2019 at the geomagnetic observatory (code AIA) of the Ukrainian Antarctic Akademik Vernadsky station. The observatory’s old magnetometric complex consisted of two LEMI-008 (No. 02 and No. 16) variometers and one POS-1 scalar magnetometer. The measurements of LEMI-008 and POS-1 were not mutually synchronized and this was one of the main problem. Every measuring instrument taken individually as a component of the whole magnetometric complex had good individual properties. However, in general, the complex as an entire system had reduced performance, mainly due to the lack of mutual synchronization of measurements. Some preliminary test results are also presented. Main objective. One of the main task of upgrading the AIA observatory was to install a new variometer that is compatible with the requirements of the 1-second INTERMAGNET data standard. For two decades, old LEMI-008 variometers at Akademik Vernadsky station have shown high baseline stability, which meets INTERMAGNET requirements. Unfortunately, the noise characteristics of old variometers, the accuracy of synchronization with UTC, and the resolution do not longer meet the current INTERMAGNET requirements for devices that produce 1-second data. Measurements of LEMI-008 variometers and POS-1 scalar magnetometer were not mutually  synchronized. Due to lack of reliable mutual synchronization, the differences between the field vector modules, calculated indirectly from the variometer measurements and measured directly with the scalar magnetometer, varied and could be unreliable. With strong geomagnetic disturbances, this reduced the overall accuracy of the magnetometric complex as an integral measuring system, although the complex consisted of high-precision instruments. Only one of LEMI-008 variometers was equipped with GPS synchronization. This made data processing difficult. Therefore, one of the crucial upgrading tasks was creation of a system for mutual synchronization of measurements provided by the variometer LEMI-025 and the scalar magnetometer POS-1 with an accuracy of approximately 0.1 s (but not worse than 1 s) using control computer. Methods. The problem of mutual synchronization of the measurements of the LEMI-025 variometer and the POS-1 scalar magnetometer (at the stage of upgrading the magnetometric complex as a whole system) was solved using a control computer by periodical adjusting the POS-1 clock and starting its measurement cycles with a given timing advance. New data arrays were obtained while the LEMI-025 magnetometer was operated in test mode. Using the Bartlett’s method and spectral harmonics averaging, the noise level of the magnetometers during a geomagnetically quiet day was estimated. The results of absolute measurements of the geomagnetic field components, regularly carried out in the observatory by two methods, were analyzed and the baselines values of the LEMI-025 magnetometer were estimated. The comparative analysis of the records of the Earth magnetic field intensity, obtained by direct measurements with a scalar magnetometer POS-1 and calculated from the baseline-adjusted components of the LEMI-025 variometer, was performed. Using the obtained baseline values and the total field difference signals the high calibration accuracy of the new variometer was confirmed and the orientation errors of its sensitivity axes in the geographical coordinate frame were estimated. Conclusions. Our preliminary results confirm that the characteristics of new LEMI-025 variometer meet the INTERMAGNET requirements. The orientation errors of LEMI-025 sensor do not exceed 5 arc minutes. The base line is quite stable. All its components have dispersion within ±2 nT, without pronounced temporal drift. The test results of LEMI-025 variometer showed that the characteristics of all magnetometric instruments in the measuring pavilion of the AIA observatory should be mutually agreed in terms of electromagnetic compatibility.